2015
DOI: 10.1111/bjh.13824
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term outcome of patients in the LRF CLL4 trial: the effect of salvage treatment and biological markers in those surviving 10 years

Abstract: SummaryWith 10+ years follow‐up in the Leukaemia Research Fund (LRF) CLL4 trial, we report the effect of salvage therapy, and the clinical/biological features of the 10‐year survivors treated for chronic lymphocytic leukaemia (CLL). Overall survival (OS) was similar in the three randomized arms. With fludarabine‐plus‐cyclophosphamide (FC), progression‐free survival (PFS) was significantly longer (P < 0·0001), but OS after progression significantly shorter, than in the chlorambucil or fludarabine arms (P < 0·00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Interestingly, in this study the majority of patients with an EBV positive biopsy had been previously treated with fludarabine. However, a hypothetic relationship between fludarabine and RS was not confirmed by recent studies that evaluated the rate of RS cases according to the type of initial therapy …”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, in this study the majority of patients with an EBV positive biopsy had been previously treated with fludarabine. However, a hypothetic relationship between fludarabine and RS was not confirmed by recent studies that evaluated the rate of RS cases according to the type of initial therapy …”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, updated results from the CLL5 trial showed a prolonged survival in patients treated with chlorambucil compared with those who received fludarabine (68.1 months versus 49.8 months, respectively) [Eichhorst et al 2009]. Similar data were reported with the long-term follow up from the CLL4 trial comparing chlorambucil with fludarabine and FC [Else et al 2015]. After 10 years observation of the survivors, OS did not differ among patients treated with chlorambucil compared with FC or the fludarabine arm; this could be explained taking into account the fact that a significantly better complete response rate was obtained following first-line chlorambucil or fludarabine progression, when compared with those who received FC as first line.…”
Section: Overview On Complement1 Trial Data and Chlorambucil-based Chmentioning
confidence: 73%
“…In randomized trials, single agent fludarabine or bendamustine have shown significant improvement over chlorambucil alone [57,58]. Combination of fludarabine with cyclophosphamide (FC) or cladribine with cyclophosphamide (CC) has shown improvement in the overall response rate (ORR) and progression free survival (PFS) compared to single agent therapy [59][60][61]. A major breakthrough came in late 1990's with the advent of rituximab.…”
Section: Evolution Of Treatment Of Cll (Then and Now In 2016)mentioning
confidence: 99%